Soil N availability, rather than N deposition, controls indirect N2O emissions. (April 2016) - Redding, M.R.; Shorten, P.R.; Lewis, R.; Pratt, C.; Paungfoo-Lonhienne, C.; Hill, J.
Abstract: Ammonia volatilised and re-deposited to the landscape is an indirect N2 O emission source. This study established a relationship between N2 O emissions, low magnitude NH4 deposition (0–30  kg N ha − 1 ), and soil moisture content in two soils using in-vessel incubations. Emissions from the clay soil peaked ( < 0.002 g N [ g soil ] − 1 min − 1 ) from 85 to 93% WFPS (water filled pore space), increasing to a plateau as remaining mineral-N increased. Peak N2 O emissions for the sandy soil were much lower ( < 5 × 10 − 5 μg N [ g soil ] − 1 min − 1 ) and occurred at about 60% WFPS, with an indistinct relationship with increasing resident mineral N due to the low rate of nitrification in that soil. Microbial community and respiration data indicated that the clay soil was dominated by denitrifiers and was more biologically active than the sandy soil. However, the clay soil also had substantial nitrifier communities even under peak emission conditions. A process-based mathematical denitrification model was well suited to the clay soil data where all mineral-N was assumed to be nitrified ( R 2 = 90 % ), providing a substrate for denitrification. This function was not well suited to the sandy soil where nitrification was much less complete. A prototype relationship representing mineral-N pool conversions (NO3 − and NH4 + ) was proposed based on time, pool concentrations, moisture relationships, and soil rate constants (preliminary testing only). A threshold for mineral-N was observed: emission of N2 O did not occur from the clay soil for mineral-N <70 mg ( kg of soil ) − 1, suggesting that soil N availability controls indirect N2 O emissions. This laboratory process investigation challenges the IPCC approach which predicts indirect emissions from atmospheric N deposition alone. Graphical abstract: Highlights: Emissions of N2 O from the clay soil, peaked from 85 to 93% WFPS. The sandy soil produced little N2 O emission peaking at 60% WFPS. Clay soil denitrifier community > clay soil nitrifier community. No clay soil emission for mineral-N <70 mg (kg of soil) −1 . Many NH4 + deposition scenarios produce emissions differing from inventory estimate.